2009
DOI: 10.1007/s10585-009-9255-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-faceted role of HSP40 in cancer

Abstract: HSP40 (DNAJ) is an understudied family of co-chaperones. The human genome codes for over 41 members of HSP40 family that reside at distinct intracellular locations. Despite their large numbers, little is known about their physiologic roles. Recent research has revealed involvement of some of the DNAJ family members in various types of cancers. In this article we summarize the information about the involvement of human DNAJ family members in various aspects of cancer biology. Furthermore we discuss the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 92 publications
0
75
0
3
Order By: Relevance
“…On the other hand, most of the HSP40 family proteins have been reported to be inversely correlated with high-grade malignancy, and HSP40 family proteins have been reported to function as tumor suppressors (40). In this study, we found that DNAJB8 was expressed in several kinds of cancer cells, including RCCs, and that it was preferentially expressed in the CSC/CIC population.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, most of the HSP40 family proteins have been reported to be inversely correlated with high-grade malignancy, and HSP40 family proteins have been reported to function as tumor suppressors (40). In this study, we found that DNAJB8 was expressed in several kinds of cancer cells, including RCCs, and that it was preferentially expressed in the CSC/CIC population.…”
Section: Discussionmentioning
confidence: 56%
“…Tid1 isoforms were also found to be involved in extra-mitochondrial protein interactions and functions (see below). These functions include regulation of cell death, proliferation, and signal transduction (Mitra et al 2009;Syken et al 1999). It was shown that the two isoforms differ in their non-mitochondrial functions due to differences in their abilities to interact with cytosolic and nuclear proteins (Lu et al 2006).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Furthermore, three stress-inducible molecular chaperones involved in protein folding, DNAJB1, DNAJB4, and DNAJB9, were increased by nifurtimox plus TM treatment. As molecular chaperones, these proteins bind to unfolded proteins or mutant proteins to ensure proper protein folding (74,75). Since oxidative stress causes the accumulation of damaged proteins, the upregulation of these genes signifies a cytoprotective response to the proteotoxic stress induced by the nifurtimox plus TM treatment.…”
Section: Discussionmentioning
confidence: 99%